2018
DOI: 10.33119/erfin.2018.3.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Environmental Quality in Nigeria: Assessing the Role of Financial Development

Abstract: In this study, we analyze the determinants of environmental quality in Nigeria, focusing on the role of financial development. It is a time series analysis covering the period from 1981 to 2016. The study uses the ARDL bounds testing approach to analyze data on urbanization, per capita income, environmental degradation, energy consumption, trade intensity, and capital investment. We generate the environmental degradation index using principal component analysis (PCA). Empirical results suggest that income, fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 42 publications
3
29
0
1
Order By: Relevance
“…(2017) and Mohiuddin et al. (2016), but supports that of Mesagan and Nwachukwu (2018) and Sekrafi and Sghaier (2018). Additionally, a bidirectional causal liaison between urbanization and CO2 emissions was disclosed.…”
Section: Discussionmentioning
confidence: 62%
“…(2017) and Mohiuddin et al. (2016), but supports that of Mesagan and Nwachukwu (2018) and Sekrafi and Sghaier (2018). Additionally, a bidirectional causal liaison between urbanization and CO2 emissions was disclosed.…”
Section: Discussionmentioning
confidence: 62%
“…Other studies including gross capital formation Zhang et al, 2021). However, studies on the relationship between energy consumption, economic growth, and environmental degradation/CO2 emissions with the inclusion of gross capital formation and trade openness simultaneously are lacking in the existing literature and needs to receive more attention in empirical analysis in the future (for example, Chen et al, 2021;Ling et al, 2015;Ekundayo Peter Mesagan & Nwachukwu, 2018;Rauf et al, 2018;Soytas et al, 2007). One corresponding study by Rauf et al (2018) found that energy consumption, economic growth, and gross capital formation positively influence CO2 emissions, while trade openness and CO2 emissions are negatively connected by applying fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) data from 47 of Belt and Road Initiative (BRI) countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One corresponding study by Rauf et al (2018) found that energy consumption, economic growth, and gross capital formation positively influence CO2 emissions, while trade openness and CO2 emissions are negatively connected by applying fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) data from 47 of Belt and Road Initiative (BRI) countries. Mesagan and Nwachukwu (2018) applied the autoregressive distributed lag (ARDL) model to study the determinants of environmental quality in the period of 1981-2016 for the case of Nigeria. The gross fixed capital formation is used as a proxy for capital investment, environmental degradation index is used to capture the environmental quality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several research that used time-series data came to the same result. For example, Moghadam and Dehbashi (2018) observed negative consequences of financial development in Iran, Sehrawat, Giri, and Mohapatra (2015) in India, Mesagan and Nwachukwu (2018) in Nigeria, and Raza and Shah (2018) in Pakistan.…”
Section: Review Of Related Literaturementioning
confidence: 99%